The Prevalance of Ear Diseases in Cat and Dogs in Kocaeli Provinces - Canpolat, İbrahim; Tanrısever, Murat; Başer, Selçuk (My University, 2022)
Objective: In this study, it was aimed to determine the prevalence of ear diseases in cats and dogs brought to clinics in Kocaeli provinces. Materials and methods: For this purpose, a general ear examination of 66 cats and 46 dogs brought to the clinic in Kocaeli were performed and the ear canal and eardrum were examined with an otoscope. In addition, a radiographic imaging method (x-ray), as well as microbiological and histopathological examinations were performed. After diagnosing the diseases, they were recorded and evaluations about ear diseases were analyzed statistically. Results: As a result, the prevalence of ear disease in cats and dogs is high in Kocaeli province; It has been determined that improving the cleaning, feeding and sheltering conditions of animals will be effective in reducing these cases, and periodic clinical examinations will enable a fast and effective treatment process by early diagnosis of these diseases.
Keywords: Cat; dog; Diagnosis; Parasites; Ear diseases